2015
DOI: 10.1039/c5ra15943a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, magnetic and catalytic oxidation properties of manganese(iii) tetrakis(ethoxycarbonyl)porphyrin

Abstract: 5,10,15,20-tetrakis(ethoxycarbonyl)porphyrin manganese(iii) chloride (MnIIITECPCl) existed as a Mn–O coordinated dimer. MnIIITECPCl gave high yield in oxidation of styrene by using TBHP or PhIO oxidant and was found recyclable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Single crystals suitable for XRD studies were grown by layering benzene over a saturated fluorobenzene solution and confirmed the structure as the Mn­(III) species, EtO PcMnCl ( 1 ) (Figure S27). Bond metrics are similar to other Mn­(III)Cl macrocyclic species, such as a similar porphyrin derivative . The high-spin, S = 2 state at Mn was confirmed by solution magnetic moment determination using the Evans method, and resulted in paramagnetically broadened resonances in the 1 H NMR spectrum.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Single crystals suitable for XRD studies were grown by layering benzene over a saturated fluorobenzene solution and confirmed the structure as the Mn­(III) species, EtO PcMnCl ( 1 ) (Figure S27). Bond metrics are similar to other Mn­(III)Cl macrocyclic species, such as a similar porphyrin derivative . The high-spin, S = 2 state at Mn was confirmed by solution magnetic moment determination using the Evans method, and resulted in paramagnetically broadened resonances in the 1 H NMR spectrum.…”
Section: Resultssupporting
confidence: 54%
“…The average C α –C β bond length for 2 + and 2 – do not vary significantly from the values of 2 (Figure S33B). Additionally, the MN bond length in both 2 + (1.526(5) Å) and 2 – (1.497(8) Å) relative to 2 (1.555(9) Å) seem to suggest little electronic participation of the metal or apical nitrogen toward these events, corroborating the solution-state spectra that suggest a highly delocalized radical residing on the ring, a common state for mono-oxidized and monoreduced macrocyclic systems. ,, …”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Over the last three decades, many efficient catalytic methodologies have been developed for the synthesis of structurally diverse epoxides . Manganese porphyrins have long been known as valuable biomimetic catalysts for oxidation of both unsaturated and saturated hydrocarbons because of their high selectivity and efficiency; in particular, epoxidation of olefins with manganese porphyrins has been extensively studied . Homogeneous catalytic media suffer from lack of recyclability, and to overcome such a problem heterogenization of such systems would be of help …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that anionic porphyrins have better membrane permeability than cationic ones [ 35 , 36 , 37 ], which may explain their higher biological activity. In order to extend the biological application scope of anionic porphyrins, two new water-soluble anionic manganese (III) and iron (III) meso -tetrakis (carboxyl) porphyrin were prepared by hydrolysis of their corresponding 5,10,15,20-tetrakis (ethoxycarbonyl) porphyrin metal complexes [ 38 , 39 ] ( Figure 1 ). The DNA binding and nuclease activity of the anionic complexes were examined by various spectral, viscosity and gel electrophoresis measurements.…”
Section: Introductionmentioning
confidence: 99%